2021
DOI: 10.1177/0033294120988104
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-Week Mindful Eating Program Applied in a Mediterranean Population With Overweight or Obesity: The EATT Intervention Study

Abstract: Background Overweight and obesity are important public health priorities. Mindful eating can contribute in preventing automatic eating behavior and emotional dysregulation, both being primary causes of overeating and negative body image. This research outlines an eight-week mindful eating intervention (i.e., project EATT) focusing on people with overweight or obesity in assisting positive behavioral, psychological and physiological change. Methods Fifty-seven people residing in Athens were recruited to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Together, focused eating and eating with awareness are two essential components of mindful eating behaviour, and should be used separately to propose the behavioural impact of the MEBS, as they may be more significant in predicting health outcomes (Franssen et al, 2020; Mantzios, 2020; Mantzios and Giannou, 2019). Hunger and satiety cues, as well as eating without distraction, represent elements that are taught in mindful eating programmes (Kristeller and Wolever, 2010; Zervos et al, 2022), but are not intrinsically elements of the eating behaviour, rest on decision making for mindful eating, and may have a different contribution altogether to health outcomes and weight regulation. Decision making for mindful eating and mindful eating behaviour should be explored separately with the MEBS, and beyond the scale, to reliably report the potential of mindful eating as a behaviour that is underpinned as a mindfulness practice.…”
Section: Discussionmentioning
confidence: 99%
“…Together, focused eating and eating with awareness are two essential components of mindful eating behaviour, and should be used separately to propose the behavioural impact of the MEBS, as they may be more significant in predicting health outcomes (Franssen et al, 2020; Mantzios, 2020; Mantzios and Giannou, 2019). Hunger and satiety cues, as well as eating without distraction, represent elements that are taught in mindful eating programmes (Kristeller and Wolever, 2010; Zervos et al, 2022), but are not intrinsically elements of the eating behaviour, rest on decision making for mindful eating, and may have a different contribution altogether to health outcomes and weight regulation. Decision making for mindful eating and mindful eating behaviour should be explored separately with the MEBS, and beyond the scale, to reliably report the potential of mindful eating as a behaviour that is underpinned as a mindfulness practice.…”
Section: Discussionmentioning
confidence: 99%
“…ME assists in the gradual change from external motivations to eat to internal motivations such as hunger when participating in ME interventions [46], promoting healthier eating behaviours [50,[52][53][54]79], including an increased intake of fruit and vegetables [22,26], and reductions in high sugar and energy dense food consumption [51,56]. Research has also found a negative association between ME and motivations to eat palatable foods such as coping and social conformity [39,45], fat and sugar consumption [48], and grazing [47,49].…”
Section: Introductionmentioning
confidence: 99%
“…Mindful eating has been found to increase the pleasure in eating, while simultaneously supporting a reduction in fat and sugar consumption, grazing, impulsive food choice, compulsive eating and motivations to eat for any other reason apart from internal feelings of hunger and satiety [19][20][21][22][23][24][25][26][27][28][29][30]. The positive outcomes have also led to several programmes targeting mindful eating, such as the Mindfulness-Based Eating Awareness Training (MB-EAT) [31] and the Mindful Eating and Living (MEAL) [32], where people suffering from other chronic conditions such as type 2 diabetes [33], chronic kidney disease [34] and obesity [30,35] benefited in improving health behaviours and outcomes.…”
Section: Introductionmentioning
confidence: 99%